Improvement of Thermal and Environmental Stabilities of Short Channel Coplanar Amorphous InGaZnO Thin‐Film Transistors by Introducing Amorphous ZrAlOx Interlayer. Issue 4 (29th October 2021) - Lee, Jiseob; Lee, Suhui; Islam, Md Mobaidul; Jang, Jin
Abstract : The short channel coplanar amorphous indium gallium zinc oxide (a‐IGZO) thin‐film transistor (TFT) is reported by introducing a ZrAlO x (ZAO) interlayer deposited by spray pyrolysis at the substrate temperature of 350 °C. The atomic ratio (at. %) of In:Ga:Zn:O is 1:2.5:1.2:5.2 in the a‐IGZO film deposited by sputtering. The a‐IGZO TFT with ZAO layer with 0.87 μm channel length exhibits the field‐effect mobility of 6.44 cm 2  V −1  s −1, the threshold voltage of −2.16 V, and on/off current ratio of 7.6 × 10 7 . It is found from the X‐ray photoelectron spectroscopy depth profile and high‐resolution transmission electron microscope analysis that some Zr atoms diffuse into the a‐IGZO underlayer. The formation of ZrO bonds on a‐IGZO surface region reduces the carrier concentration in the a‐IGZO TFT offset region, between source/drain contact and the channel, and blocks the carrier diffusion into the channel. This reduces the field‐effect mobility of 10 μm channel length TFT from 21.86 to 14.01 cm 2  V −1  s −1, but the ZAO layer protects the a‐IGZO from the diffusion of H2 O and O2 . As a result, 0.87 μm TFT shows high on/off current ratio and stable under 85 °C and 85% relative humidity test for 2 days. Abstract : Herein, a new interlayer ZrAlO x (ZAO) by spray pyrolysis for oxide thin‐film transistors (TFTs) is introduced. The ZAO layer on amorphous indium gallium zinc oxide (a‐IGZO) can protect the diffusion of water vapor and O into the a‐IGZO. Therefore, the ZAO passivated TFT with less than 1 μm channel length is stable in humid environment.